Cara Preservasi Fitoplasma dari Jaringan Kacang Tanah Bergejala Sapu untuk Deteksi DNA dengan Teknik PCR - Pulogu, Siska Irhamnawati; Mutaqin, Kikin Hamzah; Giyanto, Giyanto (Jurnal Fitopatologi Indonesia, 2017)
Witches‘ broom of peanut caused by phytoplasma is a common disease found in Indonesia. Phytoplasma is able to be detected using polymerase chain reaction (PCR) technique. One of important factor which determine the successful of phytoplasma amplification is the DNA availability from fresh tissues. The research was aimed to evaluate some preservation methods of phytoplasma from infected plant samples. The aspects to be evaluated consisted of time (1, 2, 3, and 4 weeks), temperature (-20 °C, 4 °C, and 25 °C), and preservation medium (1X PGB buffer, 3 M NaCl, CTAB buffer, 70% ethanol, non medium, and FTA-card) for storing the fresh phytoplasma infected samples. Good preservation method will optimize the phytoplasma DNA amplification using PCR standard technique followed by nested-PCR. The results showed that preservation of samples at -20 °C, 4 °C, and 25 °C in CTAB buffer was able to maintain the tissue freshness for 4 weeks and was able to provide the DNA of either quality or quantity sufficiently for PCR detection. PCR standard using a primer pair P1/P7 showed that not all of the preserved DNA of phytoplasma were amplified positively. However, standard PCR followed by nested-PCR using primer pair fU5/rU3 was able to increase the DNA detectability. Preserved samples derived from various medium and stored for 4 weeks gave positive results.  This results were in contrary with previous same samples which were detected negatively by standard PCR technique.